Cardiac remodeling and exercise tolerance in small for gestational age: a follow-up cohort study from preadolescence into adolescence - Novoa, Rommy H.; Fabijanovic, Dora; Vellvé, Kilian; Loncaric, Filip; Rodríguez-López, Mérida; Sepúlveda-Martínez, Álvaro; Sarvari, Sebastian I.; Valenzuela-Alcaraz, Brenda; Crovetto, Francesca; Faner, Rosa; Agustí, Alvar; Sitges, Marta; et al. (Frontiers in Cardiovascular Medicine, 2025)
BackgroundBeing born small for gestational age (SGA) affects 7%–10% of newborns and is associated with increased cardiovascular risk and reduced exercise capacity in adulthood with unclear underlying mechanisms. Cardiac remodeling and dysfunction occur in fetuses and children born SGA, but it is uncertain whether and how these changes persist into adolescence. The aim of the study was to assess resting cardiovascular morphology and function together with exercise tolerance in adolescents born SGA.MethodsA perinatal cohort of 30 adolescents born SGA (defined as birth weight below the 10th centile) and 28 normal birth weight controls in a tertiary university hospital in Spain was included. Participants were followed from preadolescence (age 7–12 years) into adolescence (age 12–17 years) with echocardiography and incremental cardiopulmonary exercise test (CPET).ResultsAlthough signs of cardiac remodeling and dysfunction were evident in SGA preadolescents, no significant differences in left ventricular dimensions and deformation could be demonstrated in SGA adolescents. During the follow-up period, the SGA cohort had a significantly higher increase in left ventricular (LV) base-to-apex length (SGA mean 17.61 ± 6.78 vs. controls 13.44 ± 5.12; p = 0.011), resulting in different change of LV sphericity (−0.07 ± 0.11 vs. −0.17 ± 0.14; p = 0.010). Significant differences could be observed in SGA during exercise with reduced oxygen uptake [−0.07 L/min (−0.13 to −0.005); p = 0.035], expired carbon dioxide [−0.08 L/min (−0.15 to −0.01); p = 0.033], and peak expiratory flow rate [−0.11 L/s (−0.21 to −0.01); p = 0.029].ConclusionChanges in cardiac shape and function, described in children born SGA, seem to be ameliorated in adolescence related to compensatory growth as compared to healthy controls. However, SGA adolescents had markedly reduced exercise tolerance.